Adsorptive Removal of Hg(II) from Synthetic and Real Aqueous Solutions Using Modified Papaya Seed. Issue 11 (1st November 2016) - Yadav, Sunil Kumar; Singh, Dhruv Kumar; Sinha, Shishir
Abstract : The performance of chemically modified papaya seed (CMPS) adsorbent with carboxyl and amino groups has been studied. Adsorption experiments were performed with respect to the changes in initial pH of the solution, contact time, initial Hg(II) concentration, and CMPS dosage. Kinetic data were fitted to the pseudo-second-order model. The maximum adsorption capacity calculated by Langmuir model was 18.34 mg/g. CMPS was characterized by elemental analysis, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy. The results indicate that adsorption mechanism of CMPS involves ion exchange (2Na + /Hg 2+ ) and carboxylic-group-dominated surface complexation. Regeneration study revealed that CMPS can be used successfully for four cycles with a small adsorption capacity loss (6.8%). GRAPHICAL ABSTRACT: